The Effect of Product Quality, Service Quality and Customer Relationship Management on Customer Loyalty Mediated by Customer Satisfaction of BPJS Employment Branch Office Palembang - Mariska, Lena; Helmi, Sulaiman; Gunarto, Muji; Trisninawati, Trisninawati (International Journal of Marketing & Human Resource Research, 2025)
This study examines the impact of Customer Relationship Management (CRM), Customer Satisfaction, Product Quality, and Service Quality on Customer Loyalty in a specific company. The aim is to identify the most influential factors in enhancing customer loyalty. The research employs a quantitative survey design, collecting data from 350 customers selected through a purposive sampling technique. Variables include CRM, Customer Satisfaction, Product Quality, Service Quality, and Customer Loyalty, measured using a structured questionnaire. Data analysis utilizes Structural Equation Modeling (SEM) to evaluate relationships among variables and ensure instrument validity and reliability. Key findings reveal that CRM and Customer Satisfaction significantly influence Customer Loyalty, whereas Product Quality and Service Quality show no significant effect. These results underscore the importance of CRM and Customer Satisfaction over traditional drivers, contributing valuable insights for customer retention strategies. This study highlights the evolving dynamics of loyalty in competitive markets, suggesting a shift towards relational and satisfaction-focused management.